2018
DOI: 10.1016/j.ijindorg.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Intermediaries and consumer search

Abstract: Abstract. This paper discusses how intermediaries, such as a search engine and an online marketplace, may a¤ect consumer search. We propose an analytical framework that encompasses several models of search for di¤erentiated products, with a high-quality …rm being more likely to o¤er a product that meets each consumer's need. An intermediary improves consumer search e¢ ciency by providing a search platform on which positions are sold to high-quality …rms through competitive bidding. While the intermediary may a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Better targeting leads to monopolization when there are more price shoppers, and the result is reverse if the share of price shoppers is high. 7 See also Chen and Zhang (2017), Anderson and Renault (2015) and the references therein. 8 One could assume that search cost are very high and promotional e-mails and ads provide with direct links and brand names that reduces these costs without supplying any information about products or influencing search order.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Better targeting leads to monopolization when there are more price shoppers, and the result is reverse if the share of price shoppers is high. 7 See also Chen and Zhang (2017), Anderson and Renault (2015) and the references therein. 8 One could assume that search cost are very high and promotional e-mails and ads provide with direct links and brand names that reduces these costs without supplying any information about products or influencing search order.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast,Athey and Ellison (2011),Chen and He (2011),Anderson and Renault (2015) andChen and Zhang (2017) assume that consumers know the ranking of products that they search.3 InKireyev et al (2016), the display of some product information (not prices), which is qualitatively equivalent to targeted ads as consumers pick better products, raises search conversion and encourages consumers to click on ads more frequently.4 In his field experiment with wine buyers,Fong (2017) found that consumers who obtained ads that were more tailored to their preferences searched products less on average.5 Galeotti and Moraga-González (2008) andManduchi (2004) study interesting models with homogeneous products and utility-irrelevant consumers' observable characteristics. Firms may target their ads to different-looking-identical, in all relevant characteristicsconsumers, so as to segment the market and reduce competition.6 In that paper, each consumer receives a continuum of ads, so that a visit to one firm does not allow her to infer any information about not…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, Dukes and Liu (2016) study the strategic incentives of an intermediary in the design of its search environment to lower the search costs. Chen and Zhang (2018) investigate the effect of intermediaries on consumer search and find that having an intermediary reduces consumer search costs by providing a search platform on which positions are sold to high-quality firms through competitive bidding. However, our study differs from the studies cited above in three aspects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their combined service network effectively provides the signi cant resources needed by TCs and maintains the order of local market economy(Dey and Lehner, 2017). Well-developed supporting industries and intermediary plays an important role in TCs' integration into the local market and signi cantly reduces TC's local debt ratio(Chen and Zhang, 2018). Meanwhile, there are signi cant regional differences in the types and levels of such assistant services(Holmes et al, 2012).Potential marketMarket potential is highly related to sales channels, product demand and market scale.…”
mentioning
confidence: 99%